Commercialization of Intellectual Property Assets as Intangible Cultural Heritage in the Performing Arts by Developing the National Database on Cultural Heritage in Vietnam (A Case Study on the Art of Đờn ca tài tử music and song in southern Vietnam) - Do Duy Quan, Nguyen (VNU Journal of Science: Policy and Management Studies, 2026)
Abstract: In the context of digital transformation, the cultural heritage sector is implementing digitization activities and establishing digital databases of intangible cultural heritage to serve the purposes of conservation, the promotion of heritage values, and the creation of momentum for the development of cultural industries. However, existing gaps in current intellectual property laws have posed obstacles to the commercialization of digital heritage. Adopting a systemic approach and intellectual property management, this study identifies opportunities and solutions for the commercialization of digital intangible heritage in the performing arts, using the case of the Art of Đờn ca tài tử music and song base on develope national database on cultural heritage. The research also utilizes primary data from surveys of users of digital heritage formats and management entities, demonstrating that constructing an exploitation management model grounded in intellectual property rights protection, with stakeholder coordination, will unlock opportunities to foster cultural industries and effectively commercialize digital heritage. Keywords: Commercialization, Intellectual Property Assets, Intangible Cultural Heritage, National Database on Cultural Heritage, Art of Đờn ca tài tử music and song in southern Viet Nam.